Double pigtail tube drainage for large multiloculated pyogenic liver abscesses - JinHua, Cui; YaMan, Liu; Jian, Li (Frontiers in Surgery, 2023)
Background: This study aims to investigate the efficacy and safety of double pigtail (DP) tube drainage compared with single pigtail (SP) tube drainage for the treatment of multiloculated pyogenic liver abscesses (PLA) greater than 5 cm. Patients and Methods: This study retrospectively analyzed PLA patients admitted in the Affiliated Hospital of Chengde Medical College between May 2013 and May 2021. Patients with PLAs more than 5 cm in size, who underwent drainage of the abscess with either a double pigtail or single pigtail tube, were included. Results: A total of 97 patients with PLA larger than 5 cm were studied. These included 34 patients with DP drainage and 63 patients with SP drainage. The postoperative hospital stay (13.39 ± 4.21 weeks vs. 15.67 ± 7.50 weeks; p = 0.045), and time for removal of the catheter (days) (17.23 ± 3.70 days vs. 24.11 ± 5.83 days; p = 0.038) were lower in the DP group compared with the SP group. The size of the abscess decreased to half in 21 weeks in the DP group as compared to 22 weeks in the SP group (p = 0.018). The rate of reduction, in three days, of c-reactive protein levels was 26.61 ± 14.11 mg/L/day in the DP group versus 20.06 ± 11.74 mg/L/day in the SP group (p = 0.025). The diameter of the abscess cavity at discharge was 3.1 ± 0.07 cm in the DP group as compared with 3.7 ± 0.6 cm in the SP group (p = 0.047). There was no bleeding in any of the patients despite abnormal coagulation profiles. There was no recurrence of abscess within six months of discharge and no death in the DP group. Conclusion: Double duct drainage treatment in multiloculated PLA, greater than 5 cm in size, is safe and effective.